"My portrait on the background of my dying times": the poetry of Taras Fediuk as a phenomenon of late poetic modernism (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The article deals with Taras Fedyuk’s lyrics as the phenomenon of the late poetic modernism. The distinction has been made between the aesthetic peculiarities of postmodernism and late modernism. The basic poetological peculiarities of T. Fedyuk’s artistic world in the beginning of the XXI century have been defined in the light of creative searches of the 1980s poetic generation: tendency to the symbolic aesthetics; thinking suggestion; priority of philosophic motives; accent on the topos of the South Prichernomorye as the artistic model of the small motherland. The main attention has been paid to the opening of existential lyrics discourse, connected with the loneliness existential, alienation of the individual from the world, the choice either-or and others. The artistic aspects the images embodiment of Tanatos and Eros have been analysed. The Holy Writ has been interpreted in the article as the main intertext of T.Fedyuk’s poetry: the author transforms the biblical motives and images, gives them modern sound.
Keywords: style; late modernism; postmodernism; philosophic lyrics; intertext; suggestion; landscape; image-symbol; association